Peningkatan Kemampuan Pemecahan Masalah Matematika Peserta Didik Melalui Model DMR (Diskursus Multy Representacy) di SMP Negeri 1 Langsa - Br. Sitorus, Elsha (Jurnal Dimensi Matematika, 2023)
This study to analyze the improvement of students' Mathematics problem solving ability through the DMR (Discursus Multy Reprecentacy) model at SMP Negeri 1 Langsa. The type of research approach is quantitative with Pretest-Postest Control Group Design. The population in this study was all grade VIII students of SMP Negeri 1 Langsa consisting of eleven classes with 429 students. The sample used was all students of class VIII B and VIII C as many 62 students. The instruments used are written tests and observation sheets. After the normality test was carried out in the control class, the calculate result was 0.1219 and the experimental class obtained the Lcalculate result of 0.1529 with the Ltabel value was 0.1559 so that ????ℎ???????????????????? < ???????????????????????? then H0 is accepted which means that the frequency distribution of the tested data is normal. Then homogeneity tests were carried out on the two classes and obtained results ????ℎ???????????????????? = 1,8285 and ???????????????????????? = 1,88 retrievied 1,83 < 1,88 because ????ℎ???????????????????? < ???????????????????????? then H0 is accepted and then it is concluded that the two data are homogeneous. Based on the results of the research hypothesis with value and , thereby with a significant level of 5%, H0 is rejected and H1 is accepted, so it can be concluded that there is an increase in students' Mathematics problem solving ability through the DMR (Discursus Multy Reprecentacy) model.